'What really matters to freshers?': evaluation of first year student experience of transition into university. Issue 7 (3rd October 2018) - Meehan, Catherine; Howells, Kristy
Abstract: Measuring student experience in terms of satisfaction is a national measure used by prospective students when considering their higher education choices. Increasingly league tables are used as a means to rank universities with a limited interrogation of the reality of students' experiences. This study explored the question 'What really matters to freshers?' during their transition into higher education through to completion. Students on an academic undergraduate Early Childhood Studies degree ( n = 530) over a five-year period completed a Student Experience Evaluation in their first term and this data was correlated with the National Student Survey data collected about their cohorts in the final term of their degree. During the five year period, a number of interventions were undertaken by the academic staff to develop a learning community, based on the values linked to 'being, belonging, and becoming'. The results of this study suggest that three things matter to students about their experience, that is, the academic staff they work with, the nature of their academic study and feeling like they belong. A model is proposed which aims to demonstrate the impact of academic staff, studies and the learning community that develops through social and academic experiences at University.